Status of Draught Animal Power, Shelters and Equipment in North and West Districts- a Case study in Sikkim - Tiwari, RK; Chauhan, S K; Yumnam, Jekender; Din, Deepak M (Indian Journal of Hill Farming, 2018)
The farmers in north and west Sikkim had diversified agriculture (fruits, large cardamom, ginger, paddy, maize, wheat, black gram, mustard and finger millet etc.) utilizing different breeds of draught animals (bullocks) and traditional equipment as per the information collected from the farmers. The body weight of bullock varied 219.28-374 kg and purchase price of pair of bullocks was Rs. 23000 in west Sikkim. The average number of land holdings in identified villages were 321 including 230 of marginal and small farmers. The average area dependent on one pair of bullock in west district Sikkim was worked out as 8 ha. The average population of bullocks was found 168 number in the villages of west Sikkim. The average custom hiring was 25 days in a year. The size of animal shelter varied from 2.4x2.4x2 m to 14.7x3.75x2.15 m in general. The roofs (50%) of galvanized iron sheet were common in the bullock sheds which has no sloppy concrete flooring and open from all four sides. Very few (15%) compost pits and urine disposable channels were available in the selected villages of west Sikkim. The concentrate @ 1 kg/day-bullock was found to be fed. The traditional plough (weight: 12 kg) and harness (weight: 4 kg) were common which were available in unit price of Rs 800 and Rs.500 respectively. In the north district (Mangan), the labour engaged in North Sikkim district were 29.18% of total labour engaged in cultivation in all four districts of Sikkim state. The average annual use of bullocks and labour days engaged were 40 days and 69 days in Mangan district. In north district (Mangan) the area dependable on one pair of bullocks was 1.84 ha and draught animals were only 11.15% of total population in the state. The maximum bullocks (48%) was found in west district and minimum in north district (11.15%). The traditional implements were found maximum (63.51%) in the west district (Gyalshing) and minimum (9.34%) in the north district.